From Wives to Divorcees. Separation, Divorce and Marriage Annulment in Colonial Society, Audiencia de Charcas, 1595-1640 - Presta, Ana María (Revista Complutense de Historia de América, 2016)
Marital crimes and offenses perpetrated in the private sphere were only rarely made public or led to separation, beyond the tolerated differences and iniquities obligated by duty. After the Council of Trent, matrimony became indissoluble, except in case of death of one of the spouses. Notarial documents reveal, nevertheless, the existence of female voices –expressing disappointment, discontent and pain due to abuse, adultery and betrayal- that resorted to Canon Law and justice in order to request separation, divorce or marital annulment, hopeful of acquiring ecclesiastical protection in light of the rupture of a sacramental bond.
Keywords: Marriage; Separation; Divorce; Annulment; Peru; 16-17th Centuries.